Analysis of thermodynamic data of calcium aluminate monocarbonate hydrate. (February 2019) - Bellmann, F.; Majzlan, J.; Grevel, K.-D.; Dachs, E.; Ludwig, H.-M.
Abstract: Some thermodynamic properties of calcium aluminate monocarbonate hydrate (3CaO⋅Al2 O3 ⋅CaCO3 ⋅10.7H2 O), a typical hydration product of cement were determined in this study. This includes enthalpy Δf H° = −8166.4 ± 7.7 kJ/mol, standard entropy S° = 652.4 ± 2.2 J/(mol⋅K) and heat capacity Cp ° = 716.8 ± 3.6 J/(mol⋅K) at 298.15 K. The Gibbs free energy calculated from these values is in good agreement with solubility measurements. This demonstrates that the enthalpy and entropy of phases related to cement chemistry can be correctly determined using acid solution calorimetry and low temperature relaxation calorimetry in combination with heat of dissolution reference data for CaO, calcite and AlCl3 ⋅6H2 O reported in this study.